Examining the Relationship Between Leadership and Teachers' Moral Competence: The Mediating Role of Spiritual Climate - Nouman Maqbool Rao; Chaudhary Abdul Rehman; Sami Ullah Bajwa; Nadia Nasir (Journal of Management and Research)
This research examines how workplace buoyancy, somatic burden, autonomy-supportive and autonomy-thwarting leadership styles, and spiritual climate influence the moral competency of teachers. It may ultimately contribute to the development of a positive education culture. Data was collected through a structured questionnaire completed by teachers. This study also involved machine learning techniques including Random Forest Regressor (RFR) and Gradient Boosting Regressor (GBR). These techniques aim to identify correlations between the variables. In addition, Structural Equation Modelling (SEM) was adopted to analyse direct and indirect effects. The results indicated that autonomy-supportive leadership has a positive impact on moral competence, while spiritual climate mitigates the negative impact of somatic burden on moral competence. GBR and RFR were used to evaluate features, consistently showing similar relationships, with RFR demonstrating better predictive power. This shows that the use of machine learning in analysing educational data retrieves deep patterns within the data sets. Collectively, the results of the current study imply the importance of organizational change to promote autonomy-supportive leadership and to improve the spiritual climate to increase teachers’ moral competence. There is still room for further improvement concerning the generalization of results; therefore, further studies should use a larger sample of convenience. There is a need to examine other moderators, for instance, personality traits and to incorporate longitudinal designs to evaluate effects over time.